2020
DOI: 10.3390/antiox9060484
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Analysis by HPLC-DAD of Carotenoids in Human Faeces from Spanish Adults

Abstract: Carotenoids are bioactive compounds with widely accepted health benefits. Their quantification in human faeces can be a useful non-invasive approach to assess their bioavailability. Identification and quantification of major dietary carotenoids in human faeces was the aim of the present study. Faeces and dietary intake were obtained from 101 healthy adults (45–65 years). Carotenoid concentrations were determined by HPLC in faeces and by 3-day food records in dietary intake. Carotenoids quantified in faeces (μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
(58 reference statements)
1
7
1
Order By: Relevance
“…The highest concentration in faeces in our study corresponded to β-carotene and lycopene, which are also generally more abundant in the human diet and blood [ 2 , 46 , 47 ]. The carotenoid concentration in this study was higher than that found in similar volunteers ( n = 101) in a previous study [ 26 ], and higher (more than two times the β-carotene and lycopene levels) than those described in young women ( n = 7) [ 48 ]. This can be explained by a higher intake of fruits and vegetables or, less likely, because a 24-h faecal sample was not collected and the fraction delivered to the laboratory may have had, by chance, a higher concentration of carotenoids.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The highest concentration in faeces in our study corresponded to β-carotene and lycopene, which are also generally more abundant in the human diet and blood [ 2 , 46 , 47 ]. The carotenoid concentration in this study was higher than that found in similar volunteers ( n = 101) in a previous study [ 26 ], and higher (more than two times the β-carotene and lycopene levels) than those described in young women ( n = 7) [ 48 ]. This can be explained by a higher intake of fruits and vegetables or, less likely, because a 24-h faecal sample was not collected and the fraction delivered to the laboratory may have had, by chance, a higher concentration of carotenoids.…”
Section: Discussioncontrasting
confidence: 86%
“…On the other hand, the low carotenoid bioavailability from fruits and vegetables (ca. 10–40%, [ 2 , 26 ] could also partially explain the concentrations in faeces obtained in this study, in which both non-green and green fruits and vegetables were supplied. The bioaccessibility of lutein from non-green vegetables is higher than that from green vegetables, even though they are the most abundant sources of lutein [ 49 , 50 ], which could explain the similarity in lutein elimination between the two intervention groups.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Despite most carotenoid absorption occurring within the upper gastrointestinal tract, recent research has demonstrated that some important lipid transporters involved in carotenoid uptake are located in the colon as well (Reboul, 2019). Considering the high proportion of carotenoids that reach the colon in humans (Rodríguez‐Rodríguez et al., 2020), this further substantiates the plausibility of gut microbe–carotenoid interactions.…”
Section: Introductionmentioning
confidence: 57%
“…The presence of PT and PTF in human plasma, milk, and in several tissues at levels comparable to the other major carotenoids previously mention is already known [7,38,39]. Recently, it has been reported that they account for approximately 25% of total carotenoids in adipose tissue [14] and that they are readily detected in the feces of humans [40,41]. Concerning possible health-promoting biological actions of the colorless carotenoids, there is evidence of different nature indicating that they may be involved in antioxidant and anti-inflammatory, anticarcinogenic actions [42][43][44][45][46][47][48].…”
Section: Phytoene and Phytofluene Dietary Intakes In Spanish Adult Populationmentioning
confidence: 64%